The Islamic Lunar Calendar as a Civilizational Imperative: 29 Rabi' al Awai - 1 Rabi' al Akhir/8-10 October 1991 Penang, Malaysia (American Journal of Islam and Society, 1992)
It is He Who made the sun a radiance, and the moon a light, anddetermined it by stations, that you might know the number of theyears and the reckoning (of time) ... (Qur'an 10:5).Every community possesses a personality and certain traits that distinguishit from others. The ummah of Islam was blessed by Allah MostHigh with a distinctive personality so that it could serve as a communityof the median way (wasatiyah) and as a witness (shahadah): "Thus Weappointed you a mid-most nation, so that you might be witnesses over allmankind" (2:143).In view of the important civilizational role to be played by the Muslimummah, Allah created the elements in its personality with great carein order to ensure that the expected results would come to fruition andthat the ummah would become the best community ever brought forth:"You are the best nation ever brought forth to mankind" (3:110).Among the constituent elements of the ummah's cultural and civilizattionalidentity is its perspective on time, be it past, present, or future, andhow it is to be measured. The past consists of history, from which lessonsare to be learned. The present is the current reality, every moment of whichis to be used to the best advantage or invested. The future is that which isanticipated and planned for so that it may become more resplendent.The communities that went before Islam both understood and calculatedtime in order to achieve their goals and build their civilizations. Todiffering degrees, all of them were successful in their endeavor to markthe passage of time. However, every system they devised suffered fromcalendars featuring ten months in a year, others with widely varying numbersof days in a month, calendars that began in the spring while others ...